CHARACTERISTICS OF RELATED PHYSICAL APTITUDE TO THE HEALTH OF MILITARY FIREMEN IN THE AREA OF CARIRI FROM CEARÁ, BRAZIL (Fiep Bulletin - online, 2014)
Abstract: The professions linked to the military career demand a minimum physical condition from its members, satisfactory for the acting of its specific functions, addressing them for a maintenance of good levels of physical aptitude related to the health, because in the execution of its occupation, they come across the most varied adversities, that empty space from tasks of energy worn-out bass to those that need larger physical efforts. I objectify: to characterize and to generate parameters of physical aptitude related to the military firemen's health the Methodology elapses of a descriptive, traverse study, with 24 individuals of the masculine gender of 30 to 47 years, with average of age of 35,8+4,9dp, military firemen in the cities of Juazeiro of the North and Crato, that rendered the tests of percentile of fat (%G), for cutaneous folds; to walk and to run 12 minutes; to sit down and to reach; flexion and elbow extension and to sit down and to lie (abdominal) Results: he/she met averages and DP of: %G 23,92+ 4,30; of to WALK AND to RUN 12 MIN. 2031,16+ 474,94 m; VO² MAX. 34,69+10,31 ml/kg/min; to SIT DOWN AND to REACH 33,81+10,24 cm; FLEXION is EXTENSION OF ELBOW (max. rep.) 22,13+ 11,57 rep; ABDOMINAL IN one MINUTE 20,21+11,03 rep. Conclusion: The military firemen of the area of Cariri From Ceará came with low levels of physical aptitude considering the components of force, resistance aerobics, flexibility and located muscular resistance, as well as exhibition to the risks related to the health, what can come to cause a lacuna in the execution of the mission, in presence of situations that involve so much helped him as the rescuer.
Keywords: military firemen; physical aptitude; physical tests